Enzymatic conversion of benzo(a)pyrene leading predominantly to the diol-epoxide r-7,t-8-dihydroxy-t-9,10-oxy-7,8,9,10-tetrahydrobenzo(a)pyrene through a single enantiomer of r-7, t-8-dihydroxy-7,8-dihydrobenzo(a)pyrene. - Yang, S K (1976)
Benzo(a)pyrene is metabolically and stereospecifically converted by mixed-function oxidases of rat liver microsomes and epoxide hydratase (glycol hydro-lyase (epoxide-forming), EC 4.2.1.63)to the single enantiomer (-)r-7,t-8-dihydroxy-7,8-dihydrobenzol (A) pyrene. This enantiomer is further metabolized stereoselectively by the mixed-function oxidases to predominantly the diol-epoxide, r-7,t-8-dihydroxy-t-9,10-oxy-7,8,9,10-tetrahydrobenzol(a)pyrene in which the 7-hydroxyl and the 9,10-epoxide are trans. Other unidentified metabolites are also formed from the r-7,t-8-dihydroxy-7,8-dihydrobenzo(a)pyrene. Racemic r-7,t-8-dihydroxy-7,8-dihydrobenzo(a)-pyrene is converted metabolically to both r-7,t-8-dihydroxy-t-9,10-oxy-7,8,9,10-tetrahydrobenzo(a)pyrene and r-7,t-8-dihydroxy-c-9,10-oxy-7,8,9,10-tetrahydrobenzo(a)pyrene. The diol-epoxides are unstable in aqueous medium, and their identification and characterization as r-7,t-8-dihydroxy-t-9,10-oxy-7,8,9,10-tetrahydrobenzo(a)pyrene and r-7,t-8-dihydroxy-c-9,10-oxy-7,8,9,10-tetrahydrobenzo(a)pyrene were accomplished by the identity of their tetrahydroxytetrahydrobenzo(a)pyrenes hydrolysis products with those of the authentic synthetic compounds with respect to mobility on high-pressure liquid chromatography and mass and ultraviolet absorption spectral analysis. The diol-epoxides were also reduced in the presence of NADPH to distinct trihydroxypentahydrobenzo(a)pyrenes. Since the synthetic racemic r-7,t-8-dihydroxy-t-9,10-oxy-7,8,9,10-tetrahydrobenzo(a)pyrene is very highly mutagenic in mammalian cells, we suggest that it is the metabolically formed diol-epoxide that may be an ultimate carcinogenic form of benzo(a)pyrene.